2016
DOI: 10.1037/emo0000149
|View full text |Cite
|
Sign up to set email alerts
|

Evaluative priming reveals dissociable effects of cognitive versus physiological anxiety on action monitoring.

Abstract: Effects of worry on action monitoring were trait but not state dependent, and only evidenced when actions were directly used a primes. These results suggest a double dissociation between worry and arousal during performance monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 67 publications
8
14
0
Order By: Relevance
“…VALENCE was significant, F(1, 45) = 14.46, p < .001, η 2 p = 0.24, with a higher accuracy for negative (M = 90.3, SE = 2.0) than positive words (M = 81.2, SE = 2.0). Moreover, the two-way interaction was also significant, F(1, 45) = 21.49, p < .001, η 2 p = 0.32, with a higher accuracy for negative than positive words after FAs (p tukey < 0.001), but no significant difference between negative and positive words after Hits (p tukey = 0.956), in line with a previous study performed on adults (De Saedeleer & Pourtois, 2016).…”
Section: Adults Participantssupporting
confidence: 89%
See 1 more Smart Citation
“…VALENCE was significant, F(1, 45) = 14.46, p < .001, η 2 p = 0.24, with a higher accuracy for negative (M = 90.3, SE = 2.0) than positive words (M = 81.2, SE = 2.0). Moreover, the two-way interaction was also significant, F(1, 45) = 21.49, p < .001, η 2 p = 0.32, with a higher accuracy for negative than positive words after FAs (p tukey < 0.001), but no significant difference between negative and positive words after Hits (p tukey = 0.956), in line with a previous study performed on adults (De Saedeleer & Pourtois, 2016).…”
Section: Adults Participantssupporting
confidence: 89%
“…More specifically, accumulating evidence shows that response errors are perceived by adults as negative events compared to correct responses (Koban & Pourtois, 2014;Pourtois et al, 2010; see also Dignath et al, 2019); this evaluation is rapid and automatic (Aarts et al, 2012). Using a priming methodology, it has been shown that after response errors, young adults categorize negative words faster and better than positive words, suggesting a link between these events and negative valence (see also Aarts et al, 2013, andDe Saedeleer &Pourtois, 2016, for replications). Interestingly, the reverse effect (i.e., assigning a positive value to correct responses) was much weaker in these earlier studies, suggesting an asymmetry in the affective processing of self-generated actions in adult participants.…”
Section: Errors Are Negativementioning
confidence: 99%
“…Importantly, we can rule out the possibility that this effect results from a dampened reaction to response errors in happy relative to neutral participants in general. First, the post-error slowing, which is thought to reflect an unspecific attention orienting to (deviant) response errors (Notebaert et al, 2009), and is increased by (subjective) arousal (De Saedeleer & Pourtois, 2016), was preserved in the happy mood group. Second, the ANS reaction to errors, as captured by the SCR, was preserved in happy participants.…”
Section: Discussionmentioning
confidence: 99%
“…Participants are instructed to categorize the valence of the target as quickly and accurately as possible. Several studies found faster responses for negative targets following an incongruent as compared to a congruent prime and faster response for positive targets following an congruent as compared to an incongruent prime (grasp compatibility effect: Brouillet, Ferrier, Grosselin, & Brouillet, 2011 & Pourtois, 2012& Pourtois, , 2013De Saedeleer & Pourtois, 2016). Further support for a priming of negative affect by conflict comes from an EEG study that observed an increased late positive potential for negative pictures following flanker conflict, suggesting enhanced processing of negative pictures after conflict (Ligeza & Wyczesany, 2017; but see Steinhauser, Flaisch, Meinzer, & Schupp, 2016).…”
Section: Literature Search Strategymentioning
confidence: 99%